Opposition Movement Against the Umayyad Dynasty's Rule (661-750) - Sari, Kiki Widia; Hasanah, Uswatun; fitria, fitria (El Tarikh : Journal of History, Culture and Islamic Civilization, 2023)
The Umayyad dynasty or better known as the Umayyad dynasty was the first Islamic caliphate after the end of the Khulafaur Rashidin caliphate. The duration of the reign of the Umayyad dynasty lasted from 661 to 750 ruled in the Arabian Peninsula and around the city of Damascus, then its reign in Spain from 756 to 1031 stood as the Caliphate of Cordoba. The term Umayyad dynasty refers to Umayyah bin Abdu Shams great grandfather of Muawiyah bin Abu Sufyan. In the political realm, the term "opposition" is defined as a party that opposes the representative council and opposes and criticizes a political policy of the ruling group. The name opposition is absorbed from the translation of Opposition. So in this article, we will discuss about the groups that intensified the opposition movement against the Umayyad Daulah, these groups include; The Si'ah, Mawali, Sunni, Abbasid groups.